Avaliação farmacognóstica qualitativa das folhas do vegetal Bambusa textilis - Silva, Mariana Armando da; Roder, Michelle Alexandre; Pereira, Marco Antonio dos Reis [UNESP]; Neves, Fernando Tozze Alves; Constantino, Dulce (My University, 2012)
Introduction: Bamboos belong to the family Graminae, Bambusoidae subfamily, represented by about 1,250 species worldwide. Originally employed in construction and power, are currently the subject of investigations related to its therapeutic properties in neoplasms. The main species used for therapeutic purposes based on popular knowledge are: Phyllostachys nigra; Bambusa breiflora; tuldoides Bambusa textilis and Bambusa. The literature on the therapeutic action of bamboo species is scarce, but recent studies report a promising effect in the treatment of cancer and other chronic diseases. Objective: This study aimed to evaluate qualitatively the phytochemical composition of plant extract obtained from the leaves of the bamboo species Bambusa textilis, comparing this composition from vegetable leaves with 18 and 24 months of age. Methodology: After collecting plant leaves with 18 or 24 months, they were identified and submitted to drying and milling. For qualitative analysis of its components were employed methods of macroscopic evaluation (mucilage), method of benzoin (resin), reaction Shinoda (flavonoids), reaction with gelatin solution (tannins), boiling and foaming (saponins) and jobs of reactive Wagner, Bertrand, Dragendorff, Mayer, picric acid and tannic acid (alkaloids) (Biavatti; MILK, 2007). Results: in the youngest leaves were found positive for alkaloids, flavonoids, resins and saponins. In the leaves of the plant with 24 months were found only alkaloids flavonoids and resins. Conclusion: the composition of vegetable substances were found associated with a significant therapeutic potential difference and the phytochemical composition in comparison with plant leaves 18 or 24 months. Additional studies are needed to quantify these components, as well as the clarification of its action in the fight against cancer and chronic diseases.

Introdução: Os bambus pertencem à família Graminae, subfamília Bambusoidae, representados por cerca de 1250 espécies no mundo. Originalmente empregados na construção civil e alimentação, atualmente são alvo de investigações relacionadas às suas propriedades terapêuticas em neoplasias. As principais espécies utilizadas para fins terapêuticos baseado no conhecimento popular são: Phyllostachys nigra; Bambusa breiflora; Bambusa tuldoides e a Bambusa textilis. A literatura sobre a ação terapêutica das espécies de bambu é escassa, porém estudos recentes relatam um promissor efeito no tratamento de neoplasias e outras doenças crônicas. Objetivo: O presente estudo teve como principal objetivo avaliar, qualitativamente a composição fitoquímica de extrato vegetal obtido a partir das folhas da espécie de bambu Bambusa textilis, comparando esta composição entre folhas de vegetais com 18 e 24 meses de idade. Metodologia: Após a coleta de folhas do vegetal com 18 ou 24 meses, as mesmas foram identificadas e submetidas à secagem e moagem. Para análise qualitativa de seus componentes foram empregados os métodos de avaliação macroscópica (mucilagens), método do Benjoim (resinas), reação de Shinoda (flavonóides), reação com solução de gelatina (taninos), fervura e formação de espuma (saponinas) e empregos dos reativos de Wagner, Bertrand, Dragendorff, Mayer, ácido pícrico e ácido tânico (alcalóides) (BIAVATTI; LEITE, 2007). Resultados: nas folhas mais jovens foram encontrados resultados positivos para alcalóides, flavonóides, resinas e saponinas. Nas folhas do vegetal com 24 meses foram encontrados apenas alcalóides flavonóides e resinas. Conclusão: na composição do vegetal foram encontradas substâncias associadas a um potencial terapêutico importante e uma diferença na composição fitoquímica na comparação entre folhas do vegetal com 18 ou 24 meses. Estudos adicionais são necessários para quantificar estes componentes, assim como o esclarecimento de sua ação no combate às neoplasias e doenças crônicas
Qualitative pharmacognostic evaluation of leaves of Bambusa textilis
Keywords: Bambusa textilis; Pharmacognosy; Alkaloids; Resins; Flavonoids; saponins; Bambusa textilis; Farmacognosia; Alcalóides; Resinas; Flavonóides; Saponinas